Quantitative Measurement in Vivo of Lipiodol in Lungs Especially in Connection with Lymphography - Patomäki, L. K.; Verho, S.; Torsti, R. (Nuklearmedizin - NuclearMedicine, 1974)
A new method for the quantitative determination of the radioactivity in the lungs utilizing external counting has been described. The method is based on a quick and almost complete retention in the lungs of another radioactivity labelled substance (macroaggregated 131I human serum albumin) after an intravenous injection, a fact which gives an excellent calibration of detector efficiency when the same isotope (131I) is employed.The method decribed has been applied especially to the determination of amounts of a radiological contrast material (Lipiodol) getting into the lungs in connection with a routine lymphography with the radioactive tracer method. The maximum amount of Lipiodol in the lungs was found at 24-48 hours after the lymphography, the accumulation in the lungs being 20-60% of the injected volume of Lipiodol (5 patients) and an average biological half life being 8.8 days.